Bilateral Simultaneous Revision Total Knee Arthroplasty as a Single Staged Procedure: A Case Report and Review of Literature - Vaishya, Raju (Cureus, 2017)
Bilateral revision total knee arthroplasty (TKA) is a surgical procedure, which is rarely done simultaneously as it is a difficult surgery and the safety of simultaneous bilateral single stage surgery remains unknown. We report a case of a 67-year-old woman who presented to us with bilateral painful and unstable TKA (right > left) of six months duration. The primary bilateral TKA were done 14 years ago. Bilateral simultaneous revision TKA was performed, using cemented, constrained, long-stem prostheses. The intraoperative and postoperative periods remained uneventful. At last follow-up at four years, she had a pain-free range of motion of up to 0–115°, and the patient had returned to the activities of daily living. She had stable knees with good function and no evidence of loosening or wear.